Perspectives for a study on bilingualism in Colombian regional universities - Cárdenas Vergaño, Nélida (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article reflects on the trends of bilingualism in Colombia by providing a historical overview of how the teaching of foreign languages was introduced to the country. There are also analyzed some conceptual and theoretical aspects about the definition and types of bilingualism that have influenced the proposals of the Ministry of National Education in this domain. Secondly, we describe the “Project to Strengthen Bachelor's Degrees in Languages / English”, proposed within the framework of the National Program of Bilingualism-PNB 2004-2019, in order to present the methodological foundations of the research proposal "Bilingual policies and their impact on the cultural identity and educational quality in undergraduate programs in languages – English- in Colombia, 2004-2014 ". This Project is registered in the Doctorate in Educational Sciences - Rudecolombia - CADE, Tunja, Research group History and Prospective studies Latin American Education - HISULA.